2011
DOI: 10.1016/j.fertnstert.2011.07.1010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of motile sperm organelle morphology examination (MSOME) for predicting pregnancy after intrauterine insemination

Abstract: Background: Although the motile sperm organelle morphology examination (MSOME) was developed merely as a selection criterion, its application as a method for classifying sperm morphology may represent an improvement in the evaluation of semen quality. The aim of this study was to determine the prognostic value of normal sperm morphology using MSOME with regard to clinical pregnancy (CP) after intrauterine insemination (IUI). Methods: A total of 156 IUI cycles that were performed in 111 couples were prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In the absence of consensus on 'large' vacuole definition, varying from more than 25% (Boitrelle et al, 2011) or 50% of sperm head area (Franco et al, 2008Mauri et al, 2010;Oliveira et al, 2010;Akl et al, 2011;Silva et al, 2012) to a diameter of more than 1.5 lm and visible at 4009 magnification (Watanabe et al, 2011), this cut-off has been proposed to define abnormal sperm vacuole area, using a strict objective MSOME analysis (Saïdi et al, 2008;Perdrix et al, 2012); this value represented the smallest mean vacuole area observed only in abnormal semen samples. Isolation of spermatozoa with large vacuoles was performed using spermatozoa of selected infertile patients presenting semen alterations, whereas normal Table 1 Conventional semen parameters, MSOME parameters and aneuploidy rates in MSOME selected spermatozoa considered as normal or with large vacuoles, in 10 patients and ten controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of consensus on 'large' vacuole definition, varying from more than 25% (Boitrelle et al, 2011) or 50% of sperm head area (Franco et al, 2008Mauri et al, 2010;Oliveira et al, 2010;Akl et al, 2011;Silva et al, 2012) to a diameter of more than 1.5 lm and visible at 4009 magnification (Watanabe et al, 2011), this cut-off has been proposed to define abnormal sperm vacuole area, using a strict objective MSOME analysis (Saïdi et al, 2008;Perdrix et al, 2012); this value represented the smallest mean vacuole area observed only in abnormal semen samples. Isolation of spermatozoa with large vacuoles was performed using spermatozoa of selected infertile patients presenting semen alterations, whereas normal Table 1 Conventional semen parameters, MSOME parameters and aneuploidy rates in MSOME selected spermatozoa considered as normal or with large vacuoles, in 10 patients and ten controls.…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of breast images, Ji and Kim [ 6 ] proposed to use more contextual information for breast image classification, using a convolutional neural network trained on the ICAR2018 dataset to extract tissue features and classify breast cancers into benign, in situ, and invasive breast cancers. In this paper, support vector machines are used to classify the extracted features, but large-scale breast cancer data are lacking.…”
Section: Related Workmentioning
confidence: 99%
“…According to the literature, pregnancy rates after ICSI (Bartoov et al, 2002;Antinori et al, 2008) and IUI (Akl et al, 2011) depend on the proportion of grade I spermatozoa. In the study by Akl et al (2011), patients with higher pregnancy rates had 2.5% of grade I sperm, whereas patients with low pregnancy rates presented about 1%. Even though we found here that there were few grade I/II spermatozoa after freezing-thawing, it may be of value to evaluate thawed sperm before ART.…”
Section: Morrismentioning
confidence: 99%